Pokrajina v visoki ločljivosti - Ciglič, Rok; Geršič, Matjaž; Perko, Drago; Zorn, Matija (GIS v Sloveniji, 2018)
Pokrajina v visoki ločljivosti ('The Landscape in High Resolution') is the fourteenth volume in the series GIS v Sloveniji (GIS in Slovenia). The goal of this volume is to present the wide variety of research findings on geographical information systems in Slovenia in recent years. Powerful geoinformatic tools and precise digital data facilitate research on processes and phenomena with a high level of accuracy. This makes it possible to affirm that the landscape and its components are being analyzed in high resolution. The volume clearly presents project outputs and research results in areas such as seismology, geomorphology, natural hazards, environmental protection, geography, surveying, archaeology, transport, agriculture, remote sensing, and others. Readers will discover new features regarding the applicability of geographical information systems and will learn about interesting findings in many area